Ecophysiology of Hyptis suaveolens : Germination Behaviour - Chakraborty, Dipjyoti; Mondal, Santi M.; Gupta, Kajal (Indian Forester, 2007)
Hyptis suaveolens (L.) Poit, is an etnobotanically important medicinal plant with high levels of volatile oils. The plant has been considered as an obnoxious weed and rudral species. Morphological studies show the presence of seeds of two size classes within the same plant. Higher germination percentage was recorded in the larger seeds. Germination was found to be light (positively photoblastic) and temperature (25-30Â°C) dependant. Acid scarification treatment with H2SO4 and pre-treatments with KNO3 significantly increased the germination percentage. An attempt has been made to decipher the ecophysiology of H. suaveolens by correlating germination data with ecological factors in the prevailing ecosystem.